DISPARITAS PUTUSAN HAKIM DALAM TINDAK PIDANA KORUPSI”, (STUDI PUTUSAN NOMOR:16 /PID.SUS/TKP/2017/PN.SBY, NOMOR: 126 / PID.SUSTKP/2015/PN.JKT.PST DAN NOMOR : 54/PID.B/TKP/2012/PN.JKT.PST) - Riki Rianto; Davit Rahmadan; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
One of the problems in handling corruption cases is the emergence of criminal disparities in terms of punishment. The source of the problem is the judge's decision. Judicial power as a free and independent state power on the one hand has a very positive impact on law enforcement efforts in Indonesia. In this case, the judge becomes an independent body and its decision cannot be influenced by other bodies or powers. But on the other hand, the freedom of judges in making their decisions also has a negative impact, namely the emergence of criminal disparities, such as in the case decision Number :16 /Pid.Sus/TKP/2017/PN.Sby, Number: 126 /Pid.SusTKP/2015/PN.JKT.PST and Number: 54/Pid.B/TKP/2012/PN.JKT.PST). Based on these problems, the writer is interested in knowing first, how is the examination of the judge's decision in the case of a criminal act of corruption? Second, what are the factors causing the disparity of judges' decisions in corruption cases?This type of research is classified as normative legal research with the type of legal principles. In normative legal research, the data source is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The collection of normative legal research data uses data collection techniques using library research. The data obtained through the literature study will be analyzed qualitatively. In drawing conclusions, the author uses a deductive method of thinking, namely a way of thinking that draws conclusions from a general statement or proposition into a specific statement.Based on the results of research and discussion, it can be concluded. First; criminal disparity in cases Number :16 /Pid.Sus/TKP/2017/PN.Sby, Number: 126 /Pid.Sus-TKP/2015/PN.JKT.PST and Number: 54/Pid.B/TKP/2012/ PN.JKT.PST) does not only occur in the same criminal act, but also at the level of seriousness of a criminal act, and also from the judge's decision, both by one panel of judges and by different judges for the same case. The indication can be seen from the difference in the quantity of sentencing for cases whose elements and levels of seriousness can be compared. In addition, the comparison of the amount of state losses in cases of criminal acts of corruption which is directly proportional to the number of penalties imposed for similar corruption cases can be an indicator of the occurrence of criminal disparities in corruption cases. Second, there are several factors that cause criminal disparities, especially in corruption, including the legal system factor, in the Indonesian legal system, one of the factors that can cause criminal disparities is the absence of sentencing guidelines for judges in imposing crimes and factors originating from the judge himself, the judge has very broad freedom to choose the type of criminal (stafsoort) he wants, in connection with the use of an alternative system of criminal threats in the law. Keywords: Decision Disparity - Crime - Corruption